Mobile application of Quran and Arabic language for interactive and self learning assistant: A review - Ibrahim, Noor Jamaliah; Mohd Yusoff, Mohd Yakub @ Zulkifli; Razak, Zaidi; Raja Yusof, R.J. (2012)
Mobile technology in learning process is quite demanding, nowadays. It has a huge potential as a learning tool and also can be used as distance learning environment. This kind of technology is believed able to solve the current problem in j-QAF learning, especially the Arabic and Quran learning process. It is because, the current method of Arabic and Quran learning method, become less effective and unattractive to be implemented, especially towards the young Muslim generation. Moreover, today’s busy lifestyle needs a modern and technological approach that able to optimize the study time and improve the learning process. This paper seeks to provide a comprehensive review of any recent research related to mobile application for Arabic and Quran, due to fulfill the needs of students and teachers based on the survey reports obtained. Here, the findings regarding the j-QAF students and teachers’ perceptions towards the mobile usage in Arabic Language’s and Quranic learning process will be discussed in details. Mobile learning is considered as an interactive and self-learning method, which can improve and strengthen the current learning process through utilization of portable tools or device of any mobile application. This could be another alternative due to support the existing method in learning and teaching Arabic and Quran, which can considered as advance teaching tools/aids. In current time, this mobile tool is more preferable to be used during the leisure time and suitable to be implemented with current lifestyle for self-learning and improvement method, due to optimize the study time. Areas with potential of further expansion are identified for future research in supporting the j-QAF learning.